2020
DOI: 10.21608/ejh.2020.28223.1277
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between The Therapeutic Role of Adipose Derived Mesenchymal Stem Cells and Omeprazole in Regeneration of Gastric Ulcer Induced by Aspirin in Albino Rats : Histological and Immunohistochemical Study

Abstract: Background: Aspirin induced gastric mucosal injury, which leads to gastric ulcer. Adipose Derived Mesenchymal Stem Cells (ADMSC) can be used for treatment of gastric ulcer as they can differentiate into many cell types. Omeprazole is used for treatment of gastric acid-related disorders. The Aim of the Work: Was to compare between the therapeutic role of ADSMC and omeprazole in treatment of gastric ulcer Material and Methods: Forty male albino rats were divided into four equal groups: 1-Control group. 2-Aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…In the current study, the control group revealed weak PCNA immunohistochemical reaction of the nuclei of the epithelial cells of gastric tissue of rats while the expression of immunohistochemically PCNA-stained section of the gastric tissue of rat from the GU group showed many PCNA positive nuclei of the epithelial cells of the gastric tissue. This result is consistent with recent studies showing that the gastric mucosa has strong immunoreactivity to PCNA dispersed throughout all gastric mucosal glandular (Alazzouni et al 2020 ) and epithelial cells (El-Kerdasy and Mousa 2021 ). The intense immunoreactivity to PCNA in the gastric tissue of rat in the GU group can be described as PCNA is a major indicator of tissue proliferation that occurs immediately after GU induction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the control group revealed weak PCNA immunohistochemical reaction of the nuclei of the epithelial cells of gastric tissue of rats while the expression of immunohistochemically PCNA-stained section of the gastric tissue of rat from the GU group showed many PCNA positive nuclei of the epithelial cells of the gastric tissue. This result is consistent with recent studies showing that the gastric mucosa has strong immunoreactivity to PCNA dispersed throughout all gastric mucosal glandular (Alazzouni et al 2020 ) and epithelial cells (El-Kerdasy and Mousa 2021 ). The intense immunoreactivity to PCNA in the gastric tissue of rat in the GU group can be described as PCNA is a major indicator of tissue proliferation that occurs immediately after GU induction.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the immunohistochemical staining of PCNA in the gastric tissue of rats in the ADSCs-treated group, it revealed mild positive nuclei in the epithelial cells. This finding comes in line with El-Kerdasy and Mousa ( 2021 ) who reported that the ADSCs-treated group showed mild PCNA expression in the neck cells as compared with the aspirin-induced GU group as indicated in the immunohistochemical examination. MSCs enable to rebuild injured tissue and normalize the proliferative process following re-epithelialization, differentiation, and success in GU healing (Alazzouni et al 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…The PCNA expression was substantially higher in cases of gastritis and helicobacter pylori infection [ 14 ]. Its immunostaining reactivity was also dramatically increased in gastric ulcers induced by aspirin, which was considerably lower in the omeprazole-treated group [ 84 ]. Increased PCNA expression may be related to changes in cellular proliferation, which occurs as a compensatory reaction to mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Euthanasia of animals and obtainment of gastric tissues is done 4-8 hours later [18][19][20][21] .In a study conducted by Elkerdasy et al, a different dosing regimen was employed to induce gastritis using acetylsalicylic acid (200 mg/kg). The rats, which were food-deprived overnight, received a single oral dose of 200 mg/kg of acetylsalicylic acid.…”
Section: Aspirin (Acetylsalicylic Acid)mentioning
confidence: 99%
“…The rats, which were food-deprived overnight, received a single oral dose of 200 mg/kg of acetylsalicylic acid. This dosage was administered once [21]. In a study by Abdel-Kawi et al, 25 mg/kg body weight was administered intraperitoneally [22] .…”
Section: Aspirin (Acetylsalicylic Acid)mentioning
confidence: 99%